Magnetic characteristics of LaMnO3+δ thin films deposited by RF magnetron sputtering in an O2/Ar mixture gas. (6th January 2021) - Yufeng, Chen; Wang, Geming; Zhengfeng, Sun; Shenggao, Wang; Yangwu, Mao; Quanrong, Deng; Jingjing, Yang
Abstract: In this work, LaMnO3+ δ thin films have been successfully fabricated by RF magnetron sputtering using different O2 /Ar flux ratios. The crystal structures, morphologies, stoichiometry, surface chemical states and magnetic properties of films are thoroughly characterized by x-ray powder diffraction (XRD), Raman spectrometer, scanning electron microscopy (SEM), x-ray photoelectron spectroscopy (XPS) and superconducting quantum interference device (SQUID). The magnetic characteristics of LaMnO3+ δ films are systematically studied with the transformation from Mn 3+ to Mn 4+, which is strongly controlled by the deposited O2 /Ar flux ratios. We demonstrate that LaMnO3+ δ films undergo an antiferromagnet, the coexistence of ferromagnetism and antiferromagnetism and a robust ferromagnetism ordering by the variation of Mn 3+ /Mn 4+ ratios. The LMO film deposited in pure argon atmosphere shows negligible FM signal and an inconspicuous TC . With the increase of deposited O2 /Ar flux ratios, the Curie temperature of LMO films increases from 100 K to 224 K and then decreases to 140 K and meanwhile the irreversibility temperature fluctuates between 24 K and 100 K. The appearance of cluster glass state and the unexpected exchange bias phenomenon where the film deposited at highest O2 /Ar flux ratio has a HEB  ∼ 115 Oe is observed. All these evolutions of magnetization characteristics are discussed in terms of the strength of ferromagnetic interactions and the degree of competition between ferromagnetic and antiferromagnetic interactions in LaMnO3+ δ films. Our work serves as prerequisites for LaMnO3 -based magnetic heterostructures grown by RF magnetron sputtering.